Cloning of the broadly effective wheat leaf rust resistance gene Lr42 transferred from Aegilops tauschii - Lin, Guifang; Hui Chen; Bin Tian; Sehgal, Sunish Kumar; Singh, Lovepreet K.; Jingzhong Xie; Rawat, Nidhi; Juliana, Philomin; Narinder Singh; Shrestha, Sandesh; Wilson, Duane L.; Shult, Hannah; et al. (Springer, 2022)
The wheat wild relative Aegilops tauschii was previously used to transfer the Lr42 leaf rust resistance gene into bread wheat. Lr42 confers resistance at both seedling and adult stages, and it is broadly effective against all leaf rust races tested to date. Lr42 has been used extensively in the CIMMYT international wheat breeding program with resulting cultivars deployed in several countries. Here, using a bulked segregant RNA-Seq (BSR-Seq) mapping strategy, we identify three candidate genes for Lr42. Overexpression of a nucleotide-binding site leucine-rich repeat (NLR) gene AET1Gv20040300 induces strong resistance to leaf rust in wheat and a mutation of the gene disrupted the resistance. The Lr42 resistance allele is rare in Ae. tauschii and likely arose from ectopic recombination. Cloning of Lr42 provides diagnostic markers and over 1000 CIMMYT wheat lines carrying Lr42 have been developed documenting its widespread use and impact in crop improvement.